Health care utilization by women sexual assault survivors after emergency care: Results of a multisite prospective study. Issue 1 (8th October 2020) - Short, Nicole A.; Lechner, Megan; McLean, Benjamin S.; Tungate, Andrew S.; Black, Jenny; Buchanan, Jennie A.; Reese, Rhiannon; Ho, Jeffrey D.; Reed, Gordon D.; Platt, Melissa A.; Riviello, Ralph J.; Rossi, Catherine H.; et al.
Abstract: Background: Approximately, 100, 000 US women receive emergency care after sexual assault each year, but no large‐scale study has examined the incidence of posttraumatic sequelae, receipt of health care, and frequency of assault disclosure to providers. The current study evaluated health outcomes and service utilization among women in the 6 weeks after sexual assault. Methods: Women ≥18 years of age presenting for emergency care after sexual assault to twelve sites were approached. Among those willing to be contacted for the study ( n = 1080), 706 were enrolled. Health outcomes, health care utilization, and assault disclosure were assessed via 6 week survey. Results: Three quarters (76%) of women had posttraumatic stress, depression, or anxiety, and 65% had pain. Less than two in five reported seeing health care provider; receipt of care was not related to substantive differences in symptoms and was less likely among Hispanic women and women with a high school education or less. Nearly one in four who saw a primary care provider did not disclose their assault, often due to shame, embarrassment, or fear of being judged. Conclusion: Most women receiving emergency care after sexual assault experience substantial posttraumatic sequelae, but health care in the 6 weeks after assault is uncommon, unrelated to substantive differences in need, and limited in socially disadvantaged groups. Lack of disclosure to primary care providers was common among women who did receive care.